2019
DOI: 10.32479/ijeep.8370
|View full text |Cite
|
Sign up to set email alerts
|

Transition Factors to Low Carbon Community - Engagement Initiative for Slum Communities

Abstract: Thailand has been classified as one of the ten countries that are at high risk for long-term climate change due to greenhouse gas emission, directly connected with the population size and urbanization. In 2019, Bangkok has 2,070 communities, one-third are slum communities with increasing greenhouse gas emissions. This research proposes a set of potential factors influencing community engagement initiatives to achieve a low carbon community in slum areas. The case studies on four slum communities in Bangkok by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Several studies have shown the positive effects of community participation in achieving carbon reduction, and LCC goals. For example, studies in Bangkok demonstrated the prominent role of community participation in successful low carbon city initiatives and programmes (Leknoi et al, 2022;Leknoi, 2019). Another study in China suggested that communities are essential in reducing carbon emissions (Liu et al, 2021).…”
Section: Carbon Reduction Low Carbon City and Community Participationmentioning
confidence: 99%
“…Several studies have shown the positive effects of community participation in achieving carbon reduction, and LCC goals. For example, studies in Bangkok demonstrated the prominent role of community participation in successful low carbon city initiatives and programmes (Leknoi et al, 2022;Leknoi, 2019). Another study in China suggested that communities are essential in reducing carbon emissions (Liu et al, 2021).…”
Section: Carbon Reduction Low Carbon City and Community Participationmentioning
confidence: 99%